Synthesis, antibacterial activity and interaction of DNA with lanthanide-β-cyclodextrin inclusion complexes - Polo Cerón, Dorian; Mayor-Rivera, Angélica María; Aragón-Muriel, Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this work, lanthanide complexes were synthesized starting from the corresponding La (III), Ce (III), Sm (III) and Yb (III) chlorides and cinnamate ligands which present bidentate coordination between the carboxyl group of the ligand and the lanthanide metal. These compounds were used as hosts of β-cyclodextrin to obtain new inclusion complexes by a co-precipitation method using N,N-dimethylformamide as solvent. The inclusion products were characterized by IR-ATR spectroscopy, Raman, UV-vis, 1H and 13C NMR, XRD, TGA-DSC, elemental analysis and EDTA complexometry. Antibacterial activity tests were performed using six ATTC strains (S. aureus ATCC 25923, S. aureus ATCC 29213, E. coli ATCC 25922, P. aeruginosa ATCC 27853, S. Typhimurium ATCC 14028 and K. pneumoniae ATCC BAA-2146) by the microdilution method with Mueller-Hinton broth. The results of the biological activity for the lanthanide complexes showed the synergistic effect between the lanthanide cation and the cinnamate ligand. For the inclusion complexes, a decrease of the minimum inhibitory concentration (MIC) was observed with respect to the initial lanthanide complexes. The results obtained with the bovine thymus DNA and the plasmid pBR322 DNA allow to propose an electrostatic interaction between the evaluated complexes and the molécular structure of the DNA.